Malaysian English: Language Contact and Change, Siew Imm Tan. Frankfurt am Main: Peter Lang, 2013, xvii + 241 pp. - Hajar Abdul Rahim (Kajian Malaysia, 2016)
The main thrust of this book is the evolution of Malaysian English (ME), a localised variety of English which is considered as a new variety of English within the World Englishes (WEs) framework. Evolutionary theories of new Englishes suggest that local varieties of English are the outcome of evolutionary processes that the English language experiences from the time it was transplanted until the present due to various local sociocultural and political factors. This is Tan's point of departure in investigating how ME has evolved within the Malaysian diverse cultural and linguistic scenery. The book analyses selected features of contemporary ME using a contact linguistics approach which takes into consideration the historical, linguistic, political and cultural factors that influenced the evolution of English in Malaysia throughout the period of colonial Malaya until the present. With this approach Tan argues that the evolutionary changes in ME can be observed, not just as linguistic outcomes of the contact between English and the languages of the local community, but also importantly as "manifestations of the sociohistorical aspects of the contact situation" (p. 1).